2007
DOI: 10.1128/aac.01237-06
|View full text |Cite
|
Sign up to set email alerts
|

Role for Cell Density in Antifungal Drug Resistance in Candida albicans Biofilms

Abstract: Biofilms of Candida albicans are less susceptible to many antifungal drugs than are planktonic yeast cells. We investigated the contribution of cell density to biofilm phenotypic resistance. Planktonic yeast cells in RPMI 1640 were susceptible to azole-class drugs, amphotericin B, and caspofungin at 1 ؋ 10 3 cells/ml (standard conditions) using the XTT [2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide sodium salt] assay. As reported by others, as the cell concentration increased to 1 ؋ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 61 publications
1
111
2
2
Order By: Relevance
“…C. albicans biofilms in vitro as well as in vivo are known to be resistant to all major classes of antifungal drugs except echinocandins and liposomal formulations of amphotericin B (9,21). Drug resistance has been partially attributed to increased cell density in biofilms (17). We found that despite being architecturally simpler and thinner than RPMI medium biofilms, the SU medium biofilms were still completely resistant to fluconazole and displayed increased resistance to amphotericin B.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…C. albicans biofilms in vitro as well as in vivo are known to be resistant to all major classes of antifungal drugs except echinocandins and liposomal formulations of amphotericin B (9,21). Drug resistance has been partially attributed to increased cell density in biofilms (17). We found that despite being architecturally simpler and thinner than RPMI medium biofilms, the SU medium biofilms were still completely resistant to fluconazole and displayed increased resistance to amphotericin B.…”
Section: Discussionmentioning
confidence: 59%
“…The pH was adjusted to 5.8, and the mixture was sterilized by filtration. RPMI medium (RPMI 1640 medium supplemented with L-glutamine and buffered with morpholinepropanesulfonic acid; Angus Buffers and Chemicals, Niagara Falls, NY), also containing 2% glucose (wt/vol) and adjusted to a final pH of 7.2, was used as a control for comparisons since C. albicans biofilms grown in this medium have been described by many different groups and have been extensively characterized (10,17,18).Two different in vitro models were used to assess biofilm growth and drug susceptibility. The first was a microtiter plate-based model that utilizes polystyrene, flat bottomed, 96-microtiter plates (Corning Inc.) as a substrate, as previously described (18).…”
mentioning
confidence: 99%
“…A second set of C. albicans mutants consisted of Defg1 (HLC52), the reintegrant Defg1(EFG1) (HLC74), and the corresponding wild-type (WT) CAF2 (Lo et al, 1997). Strain DSY1050, in which all major efflux pumps encoding CDR1, CDR2 and MDR1 are inactivated (Perumal et al, 2007), and corresponding WT strain SC5314 were from Gillum et al (1984). The growth medium used was yeast extract-peptone-glucose (dextrose) (YPD; 1 % yeast extract, 2 % peptone, 2 % glucose).…”
Section: Methodsmentioning
confidence: 99%
“…2). These data indicate that the miconazole sensitivity of Defg1 sessile cells is probably due to increased To determine whether efflux pumps are involved in governing miconazole tolerance of C. albicans biofilms, we investigated the miconazole sensitivity of sessile C. albicans DSY1050 cells, lacking all the major efflux pumps (CDR1, CDR2, MDR1) (Perumal et al, 2007), by using the CV quantification method as described above. We found that the miconazole sensitivity of C. albicans DSY1050 sessile cells was significantly increased compared to sessile cells of the corresponding WT SC5314 cells upon treatment with miconazole ranging from 0.15 to 2.4 mM.…”
Section: Intracellular Miconazole Levels Are Increased In Defg1 Sessimentioning
confidence: 99%
“…It is the method most commonly utilized for quantitative measurement of Candida biofilm mass, growth, and response to drug therapy (1,9,12,18,20,26,28,37). Other techniques used to assay the biofilm cell burden include [ 3 H]leucine incorporation, fluorescein diacetate, crystal violet staining, viable counts, dry weight measurements, and imaging using confocal or electron microscopy (5,8,10,35,36).…”
mentioning
confidence: 99%